Analyzing China’s Influence by China’s High-Speed Railway Diplomacy in Southeast Asia Countries - Tam Anh, Huynh Nguyen (Integrated Journal for Research in Arts and Humanities, 2024)
The Belt and Road Initiative (BRI) has drawn tremendous global attention since 2013 and the land-based Silk Road Belt is seen as the most significant part of BRI. As part of these initiatives, Chinese government has been keen to expand its high-speed railway across the country’s borders into Southeast Asia countries. In addition, China’s ambitious global infrastructure investment is backed by massive financial resources which is an endeavor to cooperate with developing countries in Asia and beyond to fortify its rising role as a global power. Yet, such cooperation is not guaranteed and some arguments claim that the debt trap and far-reaching influence over Chinese infrastructure projects are increasingly having negative impacts, even dominating the international perceptions of overseas infrastructure projects including high-speed railways implemented by Beijing. In spite of the power asymmetry between China and partner nations as well as the latter’s infrastructure investment needs, these countries need to be induced about the significant benefits of China’s high-speed railways and this creates a bargaining opportunity for developing countries in Southeast Asia. Thus, these countries could offer a sense of agency in the context of China’s influence in this region. The paper will seek to answer the following questions: What are the driving forces behind the land-based Silk Road Belt; What is the motivation for rail projects of China toward Southeast Asia nations? These findings reflect on whether we witness China’s high-speed railway diplomacy to obtain economic goals to serve their interests as well as to support China’s rising role in Southeast Asia.